Unique Brewing-Relevant Properties of a Strain of Saccharomyces jurei Isolated From Ash (Fraxinus excelsior) - Hutzler, Mathias; Michel, Maximilian; Kunz, Oliver; Kuusisto, Tiina; Magalhães, Frederico; Krogerus, Kristoffer; Gibson, Brian (Frontiers in Microbiology, 2021)
The successful application of Saccharomyces eubayanus and Saccharomyces paradoxus in brewery fermentations has highlighted the potential of wild Saccharomyes yeasts for brewing, and prompted investigation into the application potential of other members of the genus. Here, we evaluate, for the first time, the brewing potential of Saccharomyces jurei. The newly isolated strain from an ash tree (Fraxinus excelsior) in Upper Bavaria, Germany, close to the river Isar, was used to ferment a 12°P wort at 15°C. Performance was compared directly with that of a reference lager strain (TUM 34/70) and the S. eubayanus type strain. Both wild yeast rapidly depleted simple sugars and thereafter exhibited a lag phase before maltose utilization. This phase lasted for 4 and 10 days for S. eubayanus and S. jurei, respectively. S. eubayanus utilized fully the available maltose but, consistent with previous reports, did not use maltotriose. S. jurei, in contrast, utilized approx. 50% of the maltotriose available, making this the first report of maltotriose utilization in a wild Saccharomyces species. Maltotriose use was directly related to alcohol yield with 5.5, 4.9, and 4.5 % ABV produced by Saccharomyces pastorianus, S. jurei and S. eubayanus. Beers also differed with respect to aroma volatiles, with a high level (0.4 mg/L) of the apple/aniseed aroma ethyl hexanoate in S. jurei beers, while S. eubayanus beers had a high level of phenylethanol (100 mg/L). A trained panel rated all beers as being of high quality, but noted clear differences. A phenolic spice/clove note was prominent in S. jurei beer. This was less pronounced in the S. eubayanus beers, despite analytical levels of 4-vinylguaiacol being similar. Tropical fruit notes were pronounced in S. jurei beers, possibly resulting from the high level of ethyl hexanoate. Herein, we present results from the first intentional application of S. jurei as a yeast for beer fermentation (at the time of submission) and compare its fermentation performance to other species of the genus. Results indicate considerable potential for S. jurei application in brewing, with clear advantages compared to other wild Saccharomyces species.